To sell or not to sell; the differences between regulatory and community demands regarding access to antibiotics in rural Ghana - Samuel Afari-Asiedu; John Kinsman; Ellen Boamah-Kaali; Martha Ali Abdulai; Margaret Gyapong; Osman Sankoh; Marlies Hulscher; Kwaku Poku Asante; Heiman Wertheim (Taylor & Francis Group, 2018)
Background In Ghana, there is extensive over-the-counter dispensing of antibiotics, resulting in high levels of inappropriate use, and an increase in antibiotic resistance. Regulations prevent Licenced Chemical Sellers (LCS, Over-the-Counter Medicine Sellers) from selling antibiotics other than Cotrimoxazole. In practice, however, these sellers sell a variety of antibiotics. This paper aims to provide insight into the differences between regulatory and community demands on the sale of antibiotics, and to explore how these differences in demand could be resolved to facilitate safe and appropriate use of antibiotics in rural Ghana. Methods A total of 32 in-depth interviews were conducted in the Kintampo North and South Districts in Ghana; 16 among antibiotic suppliers, predominantly LCS, and 16 among community members. Six focus group discussions were also conducted among 40 community members. Data were coded using Nvivo 10 and thematically analyzed in line with study objectives. The results are presented as narratives with quotes to illustrate the findings. Results Generally, antibiotic suppliers were aware that regulations prevent LCS from selling antibiotics except Cotrimoxazole. However, LCS sell all types of antibiotics because of community demand, economic motivations of LCS, and the poor implementation of regulations that are intended to prevent them from selling these medications. Factors that influence community demand for antibiotics include previous knowledge of effectiveness of some antibiotics, delays in seeking care at health facilities, financial constraints, and distance to health facilities. LCS suggested that they should be trained and allowed to sell some types of antibiotics instead of being prevented completely from selling. Community members also suggested that Community-based Health Planning and Services (CHPS) compounds should be equipped to dispense antibiotics. Conclusion The sale of antibiotics by LCS at the community level is influenced by both structural and individual contextual factors. There is a need to educate community members on the appropriate access and use of antibiotics in rural Ghana. In addition, rather than enforcing rules that go against practice, it may be more effective to regulate the sale of antibiotics by LCS and train them to make their dispensing more appropriate. CHPS compound could also be equipped to dispense some antibiotics to improve appropriate antibiotic access at the community level.